(untitled) (Sudurpaschim Spectrum, 2026)
This paper investigates the impact of digital transformation on operational cost reduction among the small business entities. The main aim of the paper is to calibrate the perceived impact of digital transformation on operation cost reduction. The study population is defined as the business entities operating for at least for last 12 months of the survey period in Kailali and Kanchanpur District of Nepal from which samples were selected using purposive sampling within the selected strata during the period January to April 2025 to fulfil study aim. Moreover, the cross-sectional survey data from 384 small business entities were collected to calibrate their operational efficiency in cost reduction using log-linear the regression model specified as the perceived efficiency in cost reduction is the function of level of digitization, operational efficiency, firm size, expansion of sales growth, share of digital payments, and firm age. The estimated results reveal that level of digitization (β= 0.162, p < 0.05), digital payments percentage (β = 0.351, p < 0.01). However, firm age shows a weakly positive influence (β = 0.082, p < 0.10), highlighting potential learning and experience effects. Obviously, firm size has inverse effect (β = -0.337, p < 0.01) on cost efficiency. This implies diseconomies of scale in managing larger firms. In conclusion, the findings underscore the central role of level of digital transformation, density of digital payment, life span firms contribute in reducing operation cost of business entity. This research contributes to fulfil evidence gap from the less- studied spatial context and expected to offer valuable insights to policymakers and practitioners seeking to rationalize the digital transformation of small business entities of Nepal.